Evaluation of point of entry surveillance for COVID-19 at Mumbai international airport, India, July 2020 - Khyati Aroskar; Rajesh Sahu; Sushma Choudhary; Achhelal R Pasi; Pragati Gaikwad; Tanzin Dikid (Wolters Kluwer Medknow Publications, 2022)
India started Point of entry (PoE) surveillance at Mumbai International Airport, screening passengers returning from coronavirus disease (COVID-19)-affected countries using infrared thermometers. We evaluated in July 2020 for March 1-22 with the Centers for Disease Control and Prevention evaluation framework. We conducted key informant interviews, reviewed passenger self-reporting forms (SRFs) (randomly selected) and relevant Airport Health Organization and Integrated Disease Surveillance Programme (IDSP) records. Of screened 165,882 passengers, three suspects were detected and all were reverse transcription-polymerase chain reaction negative. Passengers under-quarantine line-listing not available in paper-based PoE system, eight written complaints: 6/8 SRF filling inconvenience, 3/8 no SRF filling inflight announcements, and standing in long queues for their submission. Outside staff deployed 128/150 (85.3%), and staff: passenger ratio was 1:300. IDSP reported 59 COVID-19 confirmed cases against zero detected at PoE. It was simple, timely, flexible, and useful in providing information to IDSP but missed cases at PoE and had poor stability. We recommended dedicated workforce and data integration with IDSP.